Programa De Atención E Intervención Psicosocial Orientado A La Construcción De Habilidades Psicosociales Para La Vida Desde La Gestión Del Bienestar Frente A Las Relaciones De Vida En Estudiantes Del Programa Bienvenido A La U En La Universidad Antonio Nariño (2022)
The quality of life is a set of conditions that attribute to the well-being of individuals and the realization of potentialities to achieve proposed goals in the long, medium and short term (Medina, 2016). In this aspect, the physical, material, social, emotional and developmental well-being of the subject is taken into account